The Role of Peer Interaction in Enhancing Vocabulary and Reading Skills through Digital Collaborative Platforms - Adi Bonicrono Wimrafik Banu (Indonesian Journal of Foreign Language Studies, 2025)
This study explores the role of peer interaction in enhancing vocabulary and reading skills through digital collaborative platforms, focusing on two central research questions. Firstly, it investigates how peer-interaction facilitated by digital platforms impacts students' vocabulary acquisition. Secondly, it examines students' perceptions of the effectiveness of peer interaction in digital collaborative learning environments for improving vocabulary and reading skills. The research involved 19 participants who were interviewed and observed across various educational settings. Findings indicated that peer interaction on digital platforms significantly enhances vocabulary acquisition by promoting active engagement and providing immediate feedback. Participants reported that discussions and collaborative projects facilitated deeper understanding and retention of vocabulary, while diverse perspectives from peers enriched their comprehension of reading materials. Moreover, students perceived peer interaction as highly effective, citing increased motivation and enjoyment in learning through collaborative activities. This study underscored the importance of integrating digital collaborative platforms into educational practices to foster interactive learning environments that support language skill development and student engagement.